PEMIKIRAN MUHAMMAD ABDUL MANNAN TENTANG PRODUKSI DALAM EKONOMI ISLAM - Fatimah, Siti; Trismahwati, Dewi; Pematasari, Ermanita; Selly Susanti, Septiani (EKSYDA: Jurnal Studi Ekonomi Syariah, 2023)
The objectives of this study are to find out Muhammad Abul Mannan's thoughts on Production in Islam. This research is a library research. The type of research used is qualitative. Collecting data in this study is to do documentation. The results of the analysis show that M. Abdul Mannan's thoughts on economic welfare-based production are very much in accordance with the principles of production in Islamic teachings. The fundamental principle that must always be considered in the production process is economic prosperity, the concept of economic welfare in Islam consists of increased income resulting from increased production of useful goods through the maximum use of existing resources. Comparison of Muhammad Abdul Mannan's thoughts on production in Islam with production in modern times.